Republic of Moldova : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2004 Article IV Consultation highlights that economic activity in Moldova benefited from a favorable external environment in 2003-04. GDP grew by 6.3 percent in 2003, advancing to 6.5 percent (year over year) in the first half of 2004. Large and rising workers' remittances underpinned consumption-led growth, helping consolidate Moldova's recovery from the 1998 regional crisis. Progress in structural reforms remains slow, while high transaction costs continue to hold back private sector-led growth. Some progress has been registered in fiscal reforms, and in revising the legal framework affecting investment, microfinance, audit, accounting, and leasing.